The Frankfurt Patient Safety Climate Questionnaire for General Practices (FraSiK): analysis of psychometric properties. Issue 9 (13th May 2011) - Hoffmann, Barbara; Domanska, Olga Maria; Albay, Zeycan; Mueller, Vera; Guethlin, Corina; Thomas, Eric J; Gerlach, Ferdinand M
Abstract : Background: Safety culture has been identified as having a major impact on how safety is managed in healthcare. However, it has not received much attention in general practices. Hence, no instrument yet exists to assess safety climate—the measurable artefact of safety culture—in this setting. This study aims to evaluate psychometric properties of a newly developed safety climate questionnaire for use in German general practices. Methods: The existing Safety Attitudes Questionnaire, Ambulatory Version, was considerably modified and enhanced in order to be applicable in general practice. After pilot tests and its application in a random sample of 400 German practices, a first psychometric analysis led to modifications in several items. A further psychometric analysis was conducted with an additional sample of 60 practices and a response rate of 97.08%. Exploratory factor analysis with orthogonal varimax rotation was carried out and the internal consistency of the identified factors was calculated. Results: Nine factors emerged, representing a wide range of dimensions associated with safety culture: teamwork climate, error management, safety of clinical processes, perception of causes of errors, job satisfaction, safety of office structure, receptiveness to healthcare assistants and patients, staff perception of management, and quality and safety of medical care. Internal consistency of factors is moderate to good. Conclusions: This study demonstrates the development of a patient safety climate instrument. The questionnaire displays established features of safety climate and additionally contains features that might be specific to small-scale general practices.